Espectro da Ponte Estaiada e do Mirante em meio ao Circuito do Turismo de Negócios & Eventos - Sampaio, Morgana Melca Braga (2018)
This dissertation, titled Specter of the Cable-stayed Bridge and the Observation Tower amid the Circuit of Business Tourism and Events, aims at understanding, with evaluation of public policies, a conception of touristic entrepreneurship for the city of Fortaleza through construction of urban icons, linked to the sectors that deal with it, notably the Business and Events Segment. The specific goal of this evaluation is the proposal by the Government of the State of Ceará to build the Cable-stayed Bridge and the Observation Tower as an urban icon to attract new flows of financial capital and investments directed to the sector of tourism. In spite of the non-materiality of the works, their specters support political relevance, since they were constituted within new configurations of Business Tourism & Events and agree with the prevailing lines of public policies of tourism in the State of Ceará of the last decades. The main effort of the analysis is to present a critique of the intrinsic logic applied to the conception of development of the city, starting from investments in tourism for construction of new equipment, still marked by strong State intervention that privileges the private sector, by remodeling city environs under the aegis of capital accumulation. Inspired by the "In Depth Assessment Model” developed by Rodrigues (2008), which in its construct establishes systematic rules of investigation, based on axes of analysis that guide investigative practices in the area, this dissertation reveals evaluation efforts attached to the first three analytical axes as designed by the author (content analysis of the program, context of policy formulation and institutional trajectory). This work resorted to official documents and unstructured interviews, the latter being the main investigative technique, and leading to predominantly a qualitative research. As an upshot of this option, the research plan transcended the analysis of quantitative data collected in standardized formats or in linear approaches. As a result of this evaluation, one tends to understand the metropolis as a place where urban transformations and opening of spaces march with capital reproduction and total preponderance of urban works and projects in the face of the lack of effective instruments of social controls around the set of spatial segregationist actions for obtaining profit and the consequent privilege of dominant real estate sectors. It was noticed that tourism-related policies anchor in a model of commercial urban development, inserted in the scenario of investments of public and private, national and international capital, which reveals intercession of the Business & Events Segment and the real estate sector, generating new spatial configurations, since this modality of tourism focus on works linked to major events and investments in road and leisure infrastructure.